Family money : using wills, trusts, life insurance and other financial planning tools to leave the things you own to the people you love (Silver Lake Pub., 2002)
Trends in estate planning change as often as trends in fashion. It's hard enough to earn the money to leave your loved ones ... do you have to become a lawyer just to make sure it gets to them? No. But you do need to know the basics. If you have a family, this book will help you make decisions. And, if you already have a financial advisor, it will help you measure his or her work."An excellent introduction for the general reader into the intricacies of ... wills, trusts, life insurance and other financial instruments." Midwest Book Review.